Entre a construção e a desconstrução : os discursos sobre a maternidade nas páginas da revista da semana e da fon-fon (1930-1939) - Olaisylenne dos Santos Gonçalo (2025)
The discourse of biological naturalization determines motherhood as something intrinsic to female nature, operating so that the maternal is not a questioned aspect, thus considering motherhood as a natural factor, not being influenced by cultural, economic and political aspects, which, from this perspective, would be nothing more than epiphenomena. Consequently, a normativity is generated, in which the “true woman” is configured through being a mother, and all those who lack this normativity would be considered as a deviation. In this research, I propose to observe how the maternal conception that prevails in the West is a sociocultural construction linked to social interests and needs, analyzing how maternal discourses are formulated in Revista da Semana and Fon-Fon, with the temporal cut from 1930 to 1939. The analyzes will focus on discursive practices that involve motherhood, establishing a naturalization based on the biological, with ideals of completeness and fulfillment; and the construction of maternal desire, characterized as maternal instinct, through performative acts that begin in childhood, permeating women's entire lives. Including maternal importance for social political and economic development, it becomes a central element for the formation of human capital, configuring itself as an instrument of power, exerting significant influence on social dynamics and, consequently, operating as a regulatory mechanism.